Music Quickens Time - Barenboim, Daniel 1942- (London Verso, 2008)
In this eloquent book, Daniel Barenboim draws on his profound and uniquely influential engagement with music to argue for its central importance in our everyday lives. While we may sometimes think of personal, social and political issues as existing independently of each other, Barenboim shows how music teaches that this is impossible. Turning to his intense involvement with Palestine, he examines the transformative power of music in the world, from his own performances of Wagner in Israel and his foundation, with Edward Said, of the internationally acclaimed West-Eastern Divan Orchestra. Music Quickens Time reveals how the sheer power and eloquence of music offers us a way to explore and shed light on the way in which we live, and to illuminate and resolve some of the most intractable issues of our time.
Keywords: Philosophy